The Effect of Company Characteristics on Earnings Management - Suryandari, Ni Nyoman Ayu; Susandya, AA. Putu Gede Bagus Arie; Sari, Desak Made Mya Yudia (AIBPM Publisher, 2023)
Earnings management is the action of a manager in presenting financial statements that increase (decrease) profits. This study aims to examine the effect of liquidity, profitability, firm size, leverage, and managerial ownership on Earnings management. The population in this study were 194 manufacturing companies listed on the Indonesia Stock Exchange in 2018-2020. The sample in this study were 43 companies. Determination of the sample using purposive sampling method. The analysis technique used is multiple linear regression analysis. The results showed that liquidity and firm size had no effect on Earnings management, while profitability, leverage and managerial ownership had a positive effect on Earnings management.